Control of polymerization reactors - Schurk, F. J; Deshpande, P. B; Leffew, K. W.; Nadkarni, V. M. (CRC Press, 2017)
This reference and text provides an in-depth description of developments in control techniques and their application to polymerization reactors and offers important introductory background information on polymerization reaction engineering.;Discussing modelling, identification, linear, nonlinear and multivariable schemes, Control of Polymerization Reactors: presents all available techniques that can be used to control reactors properly for optimal performance; shows how to manipulate pivotal variables that affect reactor control; examines methods for deriving dynamic process models to improve reactor efficiency; reviews reactor control problems and points out end-use properties; supplies methods for measuring process variables, and ways to estimate variables that can’t be measured; and explains how single-input, single-output (SISO) strategies can be effectively used for control.;Filled with illustrative examples to clarify concepts, including more than 730 figures, tables and equations, Control of Polymerization Reactors is intended for use as a reference for chemical, process development, process design, research and development, control systems, and polymer engineers; and polymer chemists and physicists; as well as a text for upper-level undergraduate and graduate students in polymerization reactor control courses.

Thermal and crystallization behaviour of polyphenylene sulfide in engineering polymer blends with HDPE - Nadkarni, V. M.; Shingankuli, V. L.; Jog, J. P. (International Polymer Processing, 2022)
The thermal and crystallization behaviour of polyphenylene sulfide (PPS) in its blends with high density polyethylene (HDPE) is reported. Three grades of HDPE ranging in MFI from 0.4 to 52 were used in the investigation. The effect of composition and molecular weight of HDPE on the crystallization process and morphology of PPS in the blends has been investigated by the technique of Differential Scanning Calorimetry (DSC). In the blends, PPS crystallizes in presence of molten HDPE. It is observed that the morphology of PPS in terms of crystallite size and crystallite size distribution in the blends is significantly affected by blending with HDPE. The temperature onset of melting was found to increase with increasing HDPE content and the melting peak width was found to decrease with increasing HDPE content. This indicates a larger crystallite size and a narrower crystallite size distribution of PPS in blends. The effect is more pronounced in HDPE-rich compositions. The extent of the variation in the temperature onset of melting and peak width were comparable for all the grades of HDPE. The degree of crystallinity of PPS in the blends is reduced significantly (55-70%) in HDPE-rich blends. Therefore, it is concluded that the crystallization of PPS is affected by the presence of HDPE melt. The crystallization scans of PPS in the blends, obtained in the cooling mode, did not show any evidence of accelerated nucleation. On the other hand, a marginal reduction in the temperature onset of crystallization was observed. The temperature range of crystallization of PPS in the blends was found to be less for all compositions except for 90/10 (PPS/HDPE). In summary it is concluded that blending of HDPE with PPS influences the crystal growth of PPS significantly although the effect on its homogeneous nucleation is also considerable. As a result, the morphology of PPS crystallized in blends is different from that of the homopolymer. The changes in the morphology of PPS are not sensitive to the molecular weight of HDPE probably because of the high temperature of PPS crystallization relative to the melting point of HDPE.